Malaysian national cinema : an identity crisis? / Asiah Sarji - Sarji, Asiah (UPENA, 2006)
Of late, issues of national cinema have sparked much debates and discourses in the context of Malaysian cinema. Nonetheless, the definition(s) and conception(s) of what constitutes a "Malaysian film" remain vague and unclear. There is to date still insufficient critical analysis examining how popular discourses of nationalism and national identities have shaped the development of the Malaysian film industry. This essay attempts to investigate and propose what constitutes a "Malaysian" film, arguing for the protection of a national cinema and acknowledging the critical role that films play in the process of national idealism.